Language Contact, Use And Attitudes Among The Chaldo-Assyrians Of Baghdad, Iraq: A Sociolinguistic Study (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
This study aimed at investigating the language situation among the Chaldo-Assyrians in Baghdad. The study attempted to answer the following questions: In what domains do the Chaldo-Assyrians of Baghdad use Syriac and Arabic? What are their attitudes towards both languages? To achieve the goal of this study, the researchers selected a sample that consisted of (135) Chaldo-Assyrians of different age, gender and educational background. The instruments used in this study were interviews and a questionnaire which comprised two different areas: domains of language use and language attitudes. The researchers concluded that the Chaldo-Assyrians in Baghdad used Syriac in different domains mainly at home, in religious settings and in their inner speech; and used it side by side with Arabic in many other social domains such as neighborhood, place of work, media and other public places. The study revealed that the attitudes of the Chaldo-Assyrians towards Syriac and Arabic were highly positive. Finally, the researchers recommended conducting similar studies on other ethnic groups in Baghdad like Turkumans, Kurds, Armenians and Sabians.